Beneficial yet crappy: Journalists and audiences on obstacles and opportunities in reader comments. (April 2015) - Bergström, Annika; Wadbring, Ingela
Reader comments have been a growing part of user-generated content on news sites for some 10 years now. Although activity is still relatively low, interest among the public is generally high; however, journalists still show a general resistance to audience participation. The aim of our study is to examine attitudes to reader comments from two different perspectives: the public's and the journalists'. The findings derive from one Swedish survey from each group, both of which had a response rate of about 60%. The main result shows that a large proportion of the public does not have any opinion on reader comments, but when they do, support is widespread. Furthermore, journalists have stronger opinions and are rather critical towards reader comments.